2017
DOI: 10.1136/sextrans-2016-052743
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effect of couples' HIV counselling and testing on risk reduction among Zambian HIV serodiscordant couples

Abstract: BackgroundWe present temporal trends in self-reported and biological markers of unprotected sex and sex with concurrent partners in discordant couples receiving couples' voluntary HIV counselling and testing (CVCT).MethodsHeterosexual Zambian HIV-serodiscordant couples were enrolled into longitudinal follow-up in an open cohort (1994–2012). Multivariable Anderson-Gill models explored predictors of self-report and biological indicators of unprotected sex within (including sperm on a vaginal swab, incident pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…CHTC entails simultaneous HIV testing for partners and facilitated mutual disclosure. Previous research has found that CHTC promotes sexual risk reduction, especially among serodiscordant partnerships [11][12][13] . However, despite its benefits, uptake of CHTC has remained low across multiple contexts in Sub-Saharan Africa (SSA) and specifically in South Africa.…”
Section: Resultsmentioning
confidence: 96%
“…CHTC entails simultaneous HIV testing for partners and facilitated mutual disclosure. Previous research has found that CHTC promotes sexual risk reduction, especially among serodiscordant partnerships [11][12][13] . However, despite its benefits, uptake of CHTC has remained low across multiple contexts in Sub-Saharan Africa (SSA) and specifically in South Africa.…”
Section: Resultsmentioning
confidence: 96%
“…were taken, in which the frequency of unprotected sex was reduced. A study in Zambia showed that timely intervention following diagnosis of index might be resulted in a significant decreased frequency of unprotected sexual intercourse between serodiscordant couples, as well as a significant drop in the HIV seroconversion rate [ 19 ]. Our current study showed that following diagnosis of the index case, the HIV seroconversion rate among HIV-negative partners was 1/23 of pre-diagnosis as a result of various intervention measures, which was similar to results obtained from previous research [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Couple-based HIV counseling and testing could be considered as the appropriate intervention, providing the opportunity to discuss the sexual agreement under guidance of experienced counselors. This has been proven to be effective in the potential decrease of HIV incidence among heterosexual couples in Africa [ 51 , 52 ], and it has also proven to be acceptable and safe among MSM in America [ 21 , 23 ]. Since few studies in China have focused on this aspect of HIV prevention and because there is an apparent lack of awareness existing among MSM, the development of interventions to promote open communication skills among MSM couples, such as couple-based HIV testing and counseling, is needed in China.…”
Section: Discussionmentioning
confidence: 99%